Design and feasibility of integrating personalized PRO dashboards into prostate cancer care. (9th August 2015) - Hartzler, Andrea L; Izard, Jason P; Dalkin, Bruce L; Mikles, Sean P; Gore, John L
Abstract: Objective Patient-reported outcomes (PROs) are a valued source of health information, but prior work focuses largely on data capture without guidance on visual displays that promote effective PRO use in patient-centered care. We engaged patients, providers, and design experts in human-centered design of "PRO dashboards" that illustrate trends in health-related quality of life (HRQOL) reported by patients following prostate cancer treatment. Materials and Methods We designed and assessed the feasibility of integrating dashboards into care in 3 steps: (1) capture PRO needs of patients and providers through focus groups and interviews; (2) iteratively build and refine a prototype dashboard; and (3) pilot test dashboards with patients and their provider during follow-up care. Results Focus groups ( n = 60 patients) prioritized needs for dashboards that compared longitudinal trends in patients' HRQOL with "men like me." Of the candidate dashboard designs, 50 patients and 50 providers rated pictographs less helpful than bar charts, line graphs, or tables ( P < .001) and preferred bar charts and line graphs most. Given these needs and the design recommendations from our Patient Advisory Board ( n = 7) and design experts ( n = 7), we built and refined a prototype that charts patients' HRQOL compared with age- and treatment-matched patients in personalized dashboards. Pilot testing dashboard use ( n = 12 patients) improved compliance with quality indicators for prostate cancer care ( P < .01). Conclusion PRO dashboards are a promising approach for integrating patient-generated data into prostate cancer care. Informed by human-centered design principles, this work establishes guidance on dashboard content, tailoring, and clinical use that patients and providers find meaningful.